The Impact of Adolescent Substance Use on Family Functioning: The Mediating Role of Internalizing Symptoms. Issue 4 (May 2019) - Russell, Beth S.; Simpson, Emily; Flannery, Kaitlin M.; Ohannessian, Christine M.
This longitudinal study sought to investigate associations between adolescent substance use and family functioning and whether internalizing symptoms play a mediating role in this relationship; based on growing evidence from the literature, we also explored gender differences. Participants ( N = 1, 036) completed surveys in school during 2007, 2008, and 2009. Path analysis results indicated that boys' alcohol use negatively predicted family functioning while marijuana use results indicate both significant impacts on family functioning. Further results show that boys' depressive symptoms mediated the relationships between alcohol use and family cohesion and adaptability. For girls, depressive symptoms negatively predicted family functioning (cohesion, adaptability, communication with mother/father), whereas anxiety symptoms positively predicted this same set of family functioning outcomes with the exception of communication with father.